Emoções subjetivas do acadêmico de medicina frente a morte do paciente - Macedo, Juliane (2017)
The present dissertation approaches the emotion in the subjectivity of the medicine student facing the death of the patient, based on the qualitative epistemology. The general objective of the search was to understand how medicine students experience patient’s death, trying to identify their emotions in this context and to analyze their relationships with their subjectivities in their development processes. The study was carried out at an Academic Institution in Anápolis. Three medical students, aged 24, 33 and 34, all male, chosen by lottery made in the classroom participated in the study. After they signed a Free and Informed Consent Term, these students participated in the information construction about the death of the patient, in three different empirical moments with the following resources (as Instruments): open dialogue, discussion of a clinical case and discussion of a video. The results showed that each student experiences the patient’s death in a unique way, with singular emotions, an element of their subjectivities, although in their formation process they are extensively exposed to the meaning of death in the biomedical model as an adversity that they always need to fight against. Through this result, it was concluded that medical students need to discuss in their formation process about their subjectivities and how they can face the death of the patient, a fact that most of the times is faced as failure, a mistake, even if they know that mistake is part of all humans’ life. This can help them to place themselves ethically and emotionally to exercise their profession.